Ilha da Madeira. A importância do lugar como método de aproximação ao projecto de habitação unifamiliar: 3 casos de estudo - Cláudia Sofia Sousa Caldeira (2012)
This work prepared as part of the Dissertation Master in Architecture is based in my homeland, Madeira Island, a territory with very particular characteristics which suggests that own reflections and problematics in the field of architecture. The dissertation is organized into four chapters resulting from the work methodology. Initially, and in order to clarify the PLACE, the study focuses on the context of Madeira, geographical, topographical, landscape, architecture and typically Maderian mills. It creates a kind of mental image of the island that should always be present as it passes to the following parts of the work. The second part deals with the SHAPES of popular architecture in Madeira that reveal the human capacity to adapt to Nature, as well as using the natural resources in the best way. In this chapter, we understand the several aspects connected with specific architectural concepts of sociocultural context, related to certain influences, as well as the available materials, technologies or forms of particular construction that characterizes it. The third part REFERS traditional and modern. The two concepts are no longer perceived as distant, not relatable or incompatible, but rather understood as a fundamental and complementary unit in adapting the architecture to the place. People do lectures on the dialogue between the modern and the recovery assumptions codes inherited form the past, in an attitude of mutual adjustment that gave specifics to architecture in continental territory of Portugal and in Madeira Island. The last part is the approach to architects Chorão Ramalho and Paulo David and his methods in order to know the principles and the way they perceive the architecture in the context of the island. These architects have revived the popular architecture of Madeira Island and have a deep respect for the architectural tradition of the region without, however, decline its time. This chapter is developed by analyzing three detached houses: Bianchi's house and Colonel Homem da Costa's house by Chorão Ramalho and the house in Caniço by Paulo David. The CASE STUDIES reveal the continuing legacy of popular architecture in modern and contemporary perspective. An architecture that maintains a strong connection to people and the place where it implants in, the tradition as a fundamental value of a lasting continuity open civilization, where memories never fade, but where one seeks a balance between old and new, ensuring the continuity of a universal culture.